On the complementarity of satellite surface velocity and altimetry observation networks in the Mercator ocean analysis and forecasting system: first insights - Isabelle Mirouze; Elisabeth Rémy; Giovanni Ruggiero; Mathieu Hamon; Jean-Michel Lellouche; Gérald Dibarboure; Yannice Faugère (Frontiers in Marine Science, 2026)
In recent years, the accuracy of ocean forecasts has significantly improved thanks to spatial altimetry. However, despite their importance, forecasting accurate currents is still a challenge. Therefore, satellite missions are proposed to provide measurements of surface velocity on a global coverage. The Ocean DYnamics and Surface Exchange with the Atmosphere (ODYSEA) mission of the National Aeronautics and Space Administration (NASA) and Centre National d’Etudes Spatiales (CNES) is currently competing for selection in the Earth System Explorers program. As part of the preliminary studies for ODYSEA, we have carried out Observing System Simulation Experiments (OSSEs) to assess the impact of assimilating these prospective observations in terms of Root Mean Square differences of the model state variables to a reference run. We focus on disentangling the impact of the ODYSEA observations from the impact of the observations provided by altimetry, on large scale, and checking the complementarity of these networks to avoid redundant information. We show that zonal velocity out of the Equator, sea surface height and surface salinity are mainly constrained by altimetry. Conversely, the meridional velocity is mainly constrained by velocity observations. Moreover, these latter observations help better prescribing both components of velocity at the Equator as well as the sea surface temperature in the Eastern Pacific. They also tend to significantly improve surface salinity in some regions where freshwater input occurs. Altimetry and surface velocity observations are complementary, and when they are assimilated together, all the model state variables are improved in all regions compared to assimilating altimetry only.

From Observation to Information and Users: The Copernicus Marine Service Perspective - Pierre Yves Le Traon; Antonio Reppucci; Enrique Alvarez Fanjul; Lotfi Aouf; Arno Behrens; Maria Belmonte; Abderrahim Bentamy; Laurent Bertino; Vittorio Ernesto Brando; Matilde Brandt Kreiner; Mounir Benkiran; Thierry Carval; et al. (Frontiers in Marine Science, 2019)

Requirements for an Integrated in situ Atlantic Ocean Observing System From Coordinated Observing System Simulation Experiments - Florent Gasparin; Stephanie Guinehut; Chongyuan Mao; Isabelle Mirouze; Elisabeth Rémy; Robert R. King; Mathieu Hamon; Rebecca Reid; Andrea Storto; Pierre-Yves Le Traon; Matthew J. Martin; Simona Masina (Frontiers in Marine Science, 2019)

Integrated ecological–economic fisheries models—Evaluation, review and challenges for implementation - J Rasmus Nielsen; Eric Thunberg; Daniel S Holland; Jorn O Schmidt; Elizabeth A Fulton; Francois Bastardie; Andre E Punt; Icarus Allen; Heleen Bartelings; Michel Bertignac; Eckhard Bethke; Sieme Bossier; et al. (Fish and Fisheries, 2018)
Marine ecosystems evolve under many interconnected and area‐specific pressures. To fulfil society's intensifying and diversifying needs while ensuring ecologically sustainable development, more effective marine spatial planning and broader‐scope management of marine resources is necessary. Integrated ecological–economic fisheries models ( IEEFM s) of marine systems are needed to evaluate impacts and sustainability of potential management actions and understand, and anticipate ecological, economic and social dynamics at a range of scales from local to national and regional. To make these models most effective, it is important to determine how model characteristics and methods of communicating results influence the model implementation, the nature of the advice that can be provided and the impact on decisions taken by managers. This article presents a global review and comparative evaluation of 35 IEEFM s applied to marine fisheries and marine ecosystem resources to identify the characteristics that determine their usefulness, effectiveness and implementation. The focus is on fully integrated models that allow for feedbacks between ecological and human processes although not all the models reviewed achieve that. Modellers must invest more time to make models user friendly and to participate in management fora where models and model results can be explained and discussed. Such involvement is beneficial to all parties, leading to improvement of mo‐dels and more effective implementation of advice, but demands substantial resources which must be built into the governance process. It takes time to develop effective processes for using IEEFM s requiring a long‐term commitment to integrating multidisciplinary modelling advice into management decision‐making.

Design and validation of MEDRYS, a Mediterranean Sea reanalysis over the period 1992–2013 - Mathieu Hamon; Jonathan Beuvier; Samuel Somot; Jean-Michel Lellouche; Eric Greiner; Gabriel Jordà; Marie-Noëlle Bouin; Thomas Arsouze; Karine Béranger; Florence Sevault; Clotilde Dubois; Marie Drevillon; et al. (Ocean Science, 2016)
The French research community in the Mediterranean Sea modeling and the French operational ocean forecasting center Mercator Océan have gathered their skill and expertise in physical oceanography, ocean modeling, atmospheric forcings and data assimilation to carry out a MEDiterranean sea ReanalYsiS (MEDRYS) at high resolution for the period 1992–2013. The ocean model used is NEMOMED12, a Mediterranean configuration of NEMO with a 1∕12° ( ∼ 7 km) horizontal resolution and 75 vertical z levels with partial steps. At the surface, it is forced by a new atmospheric-forcing data set (ALDERA), coming from a dynamical downscaling of the ERA-Interim atmospheric reanalysis by the regional climate model ALADIN-Climate with a 12 km horizontal and 3 h temporal resolutions. This configuration is used to carry a 34-year hindcast simulation over the period 1979–2013 (NM12-FREE), which is the initial state of the reanalysis in October 1992. MEDRYS uses the existing Mercator Océan data assimilation system SAM2 that is based on a reduced-order Kalman filter with a three-dimensional (3-D) multivariate modal decomposition of the forecast error. Altimeter data, satellite sea surface temperature (SST) and temperature and salinity vertical profiles are jointly assimilated. This paper describes the configuration we used to perform MEDRYS. We then validate the skills of the data assimilation system. It is shown that the data assimilation restores a good average temperature and salinity at intermediate layers compared to the hindcast. No particular biases are identified in the bottom layers. However, the reanalysis shows slight positive biases of 0.02 psu and 0.15 °C above 150 m depth. In the validation stage, it is also shown that the assimilation allows one to better reproduce water, heat and salt transports through the Strait of Gibraltar. Finally, the ability of the reanalysis to represent the sea surface high-frequency variability is shown.